2013
DOI: 10.1242/dev.088260
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tentacle morphogenesis in the sea anemoneNematostella vectensis

Abstract: SUMMARYEvolution of the capacity to form secondary outgrowths from the principal embryonic axes was a crucial innovation that potentiated the diversification of animal body plans. Precisely how such outgrowths develop in early-branching metazoan species remains poorly understood. Here we demonstrate that three fundamental processes contribute to embryonic tentacle development in the cnidarian Nematostella vectensis. First, a pseudostratified ectodermal placode forms at the oral pole of developing larvae and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 69 publications
4
44
0
Order By: Relevance
“…DAPT treatment during regeneration led to a block in tentacle formation (Fig. 4A and B), a phenotype also known from other cnidarians (DuBuc et al, 2014; Fritz et al, 2013; Marlow et al, 2012; Münder et al, 2013). However, as shown above, the acetylated tubulin positive oral nervous system in regenerating, Notch inhibited polyps was normal (Fig 3B).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…DAPT treatment during regeneration led to a block in tentacle formation (Fig. 4A and B), a phenotype also known from other cnidarians (DuBuc et al, 2014; Fritz et al, 2013; Marlow et al, 2012; Münder et al, 2013). However, as shown above, the acetylated tubulin positive oral nervous system in regenerating, Notch inhibited polyps was normal (Fig 3B).…”
Section: Resultssupporting
confidence: 58%
“…In hydrozoan cnidarians, however, neurons develop from non-epithelial, migratory stem cells, called i-cells, which are segregated during gastrulation (Gahan et al, 2016; Hager and David, 1997; Leclere et al, 2012; Miljkovic-Licina et al, 2007). Pharmacological inhibition of Notch signaling in adult Hydra , a hydrozoan cnidarian, revealed no effect on the numbers of adult neurons (Käsbauer et al, 2007; Khalturin et al, 2007), but this treatment did affect nematocyte differentiation and tentacle development (Käsbauer et al, 2007; Khalturin et al, 2007; Münder et al, 2013), defects that were also observed in Nematostella following pharmacological Notch inhibition (DuBuc et al, 2014; Fritz et al, 2013; Marlow et al, 2012). Hence, the role of Notch in tentacle morphogenesis and nematogenesis seems to be conserved in cnidarians, but its function in neural development requires further research across the phylum.…”
Section: Introductionmentioning
confidence: 97%
“…Within 48 hours post-fertilization, the embryo develops into a fully ciliated, free-swimming planula larva and starts to escape from its surrounding gelatin matrix. By day seven, elongated planulae settle down and metamorphose into polyps bearing four tentacles [220, 221]. Under optimal conditions, it takes 2 to 3 months for a juvenile polyp to reach sexual maturity.…”
Section: Nematostella Vectensis: Born To Be a Starletmentioning
confidence: 99%
“…In the recent years, Nematostella vectensis has become an established cnidarian model in developmental biology due to its relative ease of laboratory spawning 14,15 , tractable developmental biology 1620 , extensive regenerative capacity 2124 , and robust molecular-genetic approaches 2529 . Nematostella polyps can harbor a variable number of tentacles ranging from four to eighteen, but the common number in adulthood is sixteen 4,10 . During development, four tentacle buds simultaneously form in the swimming larvae and give rise to the initial appendages of the primary polyp 4 .…”
Section: Introductionmentioning
confidence: 99%